2006
DOI: 10.1167/iovs.06-0158
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Response Analyzer versus Goldmann Applanation Tonometry for Intraocular Pressure Measurements

Abstract: The ORA significantly overestimates IOP compared with the GAT. Differences between both sets of measures increase as the GAT-determined IOP increases. ORA readings seem to be affected by central corneal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
93
3
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 14 publications
9
93
3
12
Order By: Relevance
“…17 In a study by Pepose et al, 18 comparing the same three instruments, the DCT was the only tonometer that did not show a significant change in IOP measurement pre-and post-LASIK. The wide limits of agreement found in this study are similar to the literature for both ORA 17,19 and DCT. 20,21 There are conflicting findings in the literature regarding the difference in IOP measurement between GAT and ORA; our ORA IOPg measures were on average 1.8 mm Hg higher than the GAT pressures, similar to another study that found IOPcc to overestimate GAT by 1.7 mm Hg.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…17 In a study by Pepose et al, 18 comparing the same three instruments, the DCT was the only tonometer that did not show a significant change in IOP measurement pre-and post-LASIK. The wide limits of agreement found in this study are similar to the literature for both ORA 17,19 and DCT. 20,21 There are conflicting findings in the literature regarding the difference in IOP measurement between GAT and ORA; our ORA IOPg measures were on average 1.8 mm Hg higher than the GAT pressures, similar to another study that found IOPcc to overestimate GAT by 1.7 mm Hg.…”
Section: Discussionsupporting
confidence: 89%
“…They proceeded to refine the calculation for IOPcc, calling this new value IOPccf (corneal constant factor) and this was found to have no association with CCT. 22 Another study, performed on patients undergoing glaucoma treatment showed that ORA readings were not independent of CCT, 19 although GAT was not correlated with CCT in this study, in contrast to most published studies. In the case of the DCT, the literature has consistently showed that IOP readings are less dependent on CCT than GAT, 21,25 and our study has re-confirmed the finding.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…7 Despite its widespread use, GAT has several limitations, including confounding related to corneal thickness, calibration errors, and concerns related to contamination and sanitation. [8][9][10][11] The non-contact ocular response analyser (ORA: Reichert Ophthalmic Instruments, Buffalo, NY, USA) provides a corneal compensated IOP measurement (IOPcc) that avoids several of the imitations of GAT. 7,8,10,[12][13][14][15] The ORA has received attention in the areas of glaucoma, corneal disorders, and refractive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados em adultos, demonstraram correlação positiva entre o aumento da espessura corneana central (ECC) e os valores obtidos com cada tonômetro (8)(9)(10) . Já no que diz respeito à curvatura corneana, sabemos que há associação positiva com a PIO (11) , em que o autor chegou à conclusão que a cada 3 dioptrias há aumento de 1 mmHg na PIO.…”
Section: Introductionunclassified